2021
DOI: 10.1021/acsnano.1c05612
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Chameleon Skin with Super-Sensitive Thermal and Mechanochromic Response

Abstract: Both the nonclose-packed structure and the large refractive index contrast of guanine nanocrystals and cytosols in iridophores play a vital role in the dynamic camouflage of chameleons, including the bright skin color and color tuning sensitivity to external stimulus. Here, the nonclose-packed photonic crystals consisting of ZnS nanospheres and polymers, which have similar refractive indices with guanine nanocrystals and cytosols, respectively, are constructed by a twostep filling strategy. ZnS@SiO 2 nanospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
100
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 64 publications
1
100
0
Order By: Relevance
“…The 2D and 3D angleresolved reflection spectra (Figure S1(c)) of the PC paper show that its reflection wavelength blue shifts from 480 to 393 nm and the corresponding color changes from blue to purple (Figure S1(d)) when the incident and detection angle decrease from 0 to 60 °simultaneously, further verifying the long-range ordered structures of the PC paper. These results firmly demonstrated that the PC paper possesses highly ordered and nonclosely packed structures similar to those of chameleon skins [71][72][73][74].…”
Section: Characterization Of Chameleon-inspired Swellable Andsupporting
confidence: 70%
“…The 2D and 3D angleresolved reflection spectra (Figure S1(c)) of the PC paper show that its reflection wavelength blue shifts from 480 to 393 nm and the corresponding color changes from blue to purple (Figure S1(d)) when the incident and detection angle decrease from 0 to 60 °simultaneously, further verifying the long-range ordered structures of the PC paper. These results firmly demonstrated that the PC paper possesses highly ordered and nonclosely packed structures similar to those of chameleon skins [71][72][73][74].…”
Section: Characterization Of Chameleon-inspired Swellable Andsupporting
confidence: 70%
“…[19] The structural color, generated by the interaction between light and ordered micro-nano structures, has the advantages of strong stability, continuous change, and ease of regulation. [22][23][24][25] Thereby, combining structural color with ionogels provides a promising strategy to construct I-skins with synchronous electrical and optical signals, in which the ionic signal offers precise sensing capability and the color change provides visual information, allowing for higher-level applications including multifunctional sensing, visualized dynamic displays, and direct intelligent interactions with users. However, the relevant research is still in its infancy and rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the self-assembled colloidal crystals (CCs) have offered unprecedented opportunities, because of their cheap cost, facile preparation procedures, the comparative simplicity of scaling up, and flexibility of building complicated nanometer-precision architectures 14 , 15 . In particular, the non-close-packed CCs formed by the charge repulsion of highly charged nanoparticles are attracting great interest for their relatively simple fabrication and flexible color adjustment 16 . Benefitting from these advantages, a variety of functional structurally colored materials have been fabricated for displaying 17 , anti-counterfeiting 18 , coding 19 , 20 , etc 21 .…”
Section: Introductionmentioning
confidence: 99%